New Targets for Immune Inflammatory Response in Rheumatoid Arthritis: Focus on the Potential Significance of N6-Methyladenosine, Ferroptosis and Cuproptosis - Wang S; Wan L; Zhang M; Yan D; Li F (Journal of Inflammation Research, 2025)
Siyu Wang,1 Lei Wan,1,2 Mengyu Zhang,1 Dawei Yan,1 Feng Li1 1First Clinical Medical College, Anhui University of Traditional Chinese Medicine, Hefei, Anhui, 230038, People’s Republic of China; 2Department of Rheumatology, First Affiliated Hospital of Anhui University of Traditional Chinese Medicine, Hefei, Anhui, 230031, People’s Republic of ChinaCorrespondence: Lei Wan, Email yxwanlei@163.comAbstract: Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovitis. It has a high prevalence worldwide, significantly impacting patients ‘ quality of life. There are still numerous obstacles and problems in the treatment of this disease. In the RA patients and RA animal models, the inflammatory response mainly involves abnormal activation of immune cells, such as T cells and macrophages. These cells release pro-inflammatory cytokines and trigger autoimmune reactions, ultimately causing irreversible joint tissue damage. The pathogenesis of RA is complex, involving genetic and environmental factors. Genetic factors increase the risk of disease, while environmental factors, such as infection and smoking, can trigger the onset of disease. An in-depth study of its pathogenesis and new therapeutic targets is of great significance in improving the therapeutic effect of RA. Recently, m6A methylation, an RNA modification method, has played an important role in regulating gene expression and disease progression. This modification significantly regulates immune inflammatory responses in RA, providing new insights for potential therapeutic approaches. Moreover, ferroptosis and cuproptosis, two new forms of cell death, have gradually been recognized to play an important role in the pathogenesis of RA. Ferroptosis is characterized by an imbalance in intracellular iron homeostasis and the production of reactive oxygen species, while cuproptosis involves the accumulation and metabolic abnormalities of intracellular copper. These processes play a key role in the immune inflammatory response of RA and have become potential therapeutic targets. The current review discusses the research progress of m6A methylation, ferroptosis, and cuproptosis in the pathogenesis of RA and elucidates their interactions. An in-depth understanding of these new targets might provide new strategies and drug design ideas for the treatment of RA, thereby improving the prognosis and quality of life of RA patients.Keywords: rheumatoid arthritis, immune inflammation, n6-methyladenosine, ferroptosis, cuproptosis